IDIOM POPULER BAHASA MELAYU JAMBI DIALEK MELAYU BUNGO - Dodi Oktarizaa; Dedi Efendi (Universitas Muara Bungo, 2018)
This research is aimed to gather and describe the forms of idiom and its meaning that used by the speaker of Jambi Malay Language Bungo Malay Dialect. There are three steps conducted in the research, they are collecting data, analyzing data, and presenting the result of analysis.Incollecting data, the method that is used known as observational and conversational method, by applying some techniques, namely non participant observational technique, note taking, record, and elicitation technique.Then, in analyzing data, the writer used descriptive qualitative approach in order to explain the forms and their meaning that resulted from the idioms.In addition, the writer also applay referential method in analyzing that can connect and compare the elements that belong to language itself.Moreover, the writer used informal method for presenting the result of analysis.By applying morphological approach in doing analysis, the writer found that idioms derived from the combination of lexeme outcome some parts of speech ,namely adjective is 28 words, noun is 27 words, and verb is only 17 words. Finally, the writer concludes that the idiom expression that used by Jambi Malay Language Bungo Malay Dialect speakers is mostly belong to adjective and noun . The appearance of these two kinds of parts of speech can be stated as the explanation of the condition and the nature of its topic from the speakers in communication process Keywords: Morphology, Idiom, Jambi Malay Language, Bungo Malay Dialect, Parts of Speech